46. ASSOCIATION OF LOW-CARBOHYDRATE DIETARY HABIT AND BLOOD PRESSURE. (May 2021) - Harlyjoy, Beta Canina; Widyantoro, Bambang; Sukmawan, Renan
Abstract : Background: Hypertension is a major risk factor for cardiovascular events. Several studies have shown dietary modification as one of the cornerstones in the non-pharmacological intervention in patients with hypertension. Alas, the recommended macronutrients diet is still at dispute. Objective: This study aimed to observe the association between the macronutrient components of dietary habit and blood pressure. Methods: This study was conducted in the district of Natuna, in July 2019. Dietary habit was obtained through food recall, on which each patient was thoroughly interviewed regarding their food consumption for 2 days, 1 representing weekday and 1 for the weekend. Blood pressure reading was taken 3 times, with the hypertension status was determined by the average of 2 nd and 3 rd readings. Results: Two hundred and one patients were included in this study. In our populations, the hypertension rate was 78.6%. Those with hypertension showed lower energy intake (1026: 313–3547 vs 1070: 430–3348 calories per day, p  = 0.651), lower protein intake (0.65: 0.20–4.89 vs 0.75: 0.21–2.61 g/kg body weight, p  = 0.238), higher fat intake (20.55 ± 7.66 vs 19.6 ± 7.37% of calories intake, p  = 0.691), and slightly lower carbohydrate intake (61.56 ± 10.4 vs 61.58 ± 8.5% of calories intake, p  = 0.641). Chi-square analysis found that carbohydrate intake more than 45% of daily calories was associated with hypertension ( p  = 0.039) with odds ratio of 4.026, 95% CI of 1.109–14.619 ( p  = 0.034). Conclusion: Carbohydrate intake more than 45% of daily calories intake is associated with hypertension.